Helicobacter pylori lipopolysaccharide structural domains and their recognition by immune proteins revealed with carbohydrate microarrays. (1st February 2021) - Silva, Lisete M.; Correia, Viviana G.; Moreira, Ana S.P.; Domingues, Maria Rosário M.; Ferreira, Rui M.; Figueiredo, Céu; Azevedo, Nuno F.; Marcos-Pinto, Ricardo; Carneiro, Fátima; Magalhães, Ana; Reis, Celso A.; Feizi, Ten; et al.
Graphical abstract: Highlights: LPSs from H. pylori clinical isolates triggering gastric pathologies were studied. LPSs were structurally analyzed by GC-MS, ESI-MS n and microarrays. Ribans were detected in all clinical isolates but not in the reference strain 26695. DC-SIGN recognized all H. pylori LPSs while galectin-3 specifically recognized two 3-Gal-rich clinical isolates. High IgG antibody levels to H. pylori LPSs were observed in sera from H. pylori -infected cases. Abstract: The structural diversity of the lipopolysaccharides (LPSs) from Helicobacter pylori poses a challenge to establish accurate and strain-specific structure-function relationships in interactions with the host. Here, LPS structural domains from five clinical isolates were obtained and compared with the reference strain 26695. This was achieved combining information from structural analysis (GC-MS and ESI-MS n ) with binding data after interrogation of a LPS-derived carbohydrate microarray with sequence-specific proteins. All LPSs expressed Lewis x/y and N -acetyllactosamine determinants. Ribans were also detected in LPSs from all clinical isolates, allowing their distinction from the 26695 LPS. There was evidence for 1, 3-d -galactans and blood group H-type 2 sequences in two of the clinical isolates, the latter not yet described for H. pylori LPS. Furthermore, carbohydrate microarray analyses showed a strain-associated LPS recognition by the immune lectins DC-SIGN and galectin-3 and revealed distinctive LPS binding patterns by IgG antibodies in the serum from H. pylori -infected patients.